Influence of different polishing and aging periods on the surface roughness of composite resins (Research, Society and Development, 2021)
The aim of this study was to evaluate the influence of the polishing period on surface roughness (Ra) before and after thermal aging in four composite resins - CR (Durafill VS, Vittra APS, Filtek Z350XT and Spectra Smart). This in vitro study evaluated: (1) CR in 4 levels; (2) polishing period (PP) in three levels (immediate, 7 and 14 days) and (3) artificial aging in two levels: without aging and after 10,000 cycles. For this, 240 CR specimens were allocated into 12 groups (n=20) according to PP with SofLex Pop On disks.  For Ra, 3 measurements on the top surface of each specimen were performed with a diamond tip and constant load of 4mN and 0.25mm/s. Next, the specimens were aged in thermocycling, with temperatures of 5° and 55°C, during 30 seconds in each temperature, and repeated testing afterwards. The data were submitted to statistical tests with 5% significance. The alteration in Ra was observed only in the late polishing in the period of 7 days, where the Durafill VS CR showed higher Ra in comparison to the other CRs. After thermocycling, the groups showed significant difference only with late polishing in the 21-day period; the nanoparticulated RCs (Z350XT˂Vittra APS) recorded the highest Ra values, followed by the microhybrid (DurafillVS) and nanohybrid (Spectra Smart) RCs, respectively. Thus, late polishing in the 7-day and immediate period provided higher Ra values, especially for the nanohybrid and microhybrid composite resins.